Enhancing the Problem Solving Skills of Decision Science Learners - Cheng, Sheila; Fung, Han Ping (AeU, 2015)
With the increasing complexity of our society, problem solving skills have been admittedly acknowledged by employers as one of the critical and crucial soft skills sought-after attributes in their recruitment of employees. Many studies have claimed that decision makers need to possess different problem solving skills to approach and solve different types of problems. How can a person's solving skills be enhanced to the level that could lead to better decisions in an organization? Decision Science is a discipline which intends to help decision-makers to think more clearly about complex issues in their organisations, and on achieving committed alignment of key players. This paper attempts to explore the cognitive processes of successful problem solvers in solving the Decision Science problems. A sample of 42 undergraduate business degree students was used in this study in solving both well-structured and ill- structured Decision Science problems. „Think aloud ‟ approach was audio- and video- recorded in the problem solving sessions. Results revealed that the cognitive processes of successful solvers followed a set of algorithms. This provides an insight for educators and instructional designers to enhance learners‟ problem solving skills in their formal education.